The Role of Local Government and Multi-Stakeholder Collaboration in Reducing Structural Poverty: An Evaluation Study of SDGS to Overcome Poverty in Sidoarjo Regency - Nisfatun Choiriyah; Andin Arfi Aurellia; Indah Prabawati; Firre An Suprapto (Income Journal Of Economics Development, 2026)
This study aims to analyze the role of local governments and multi-stakeholder collaboration in reducing structural poverty through the evaluation of the implementation of the Sustainable Development Goals (SDGs) of the first goal (No Poverty) in Sidoarjo Regency. The method used is a descriptive qualitative approach with literature studies, analysis of regional policy documents, and analysis of secondary data from the Central Statistics Agency (BPS) and local government reports. The results of the study show that the Sidoarjo Regency Government has integrated the SDGs targets into regional development planning through social assistance programs, MSME empowerment, and increased access to education and health. However, challenges are still found in aspects of structural poverty such as inequality in access to decent work and distribution of resources. Collaboration between government, the private sector, academia, and civil society has been proven to contribute to expanding the reach of programs and increasing the effectiveness of interventions. In conclusion, reducing structural poverty requires strengthening cross-sectoral synergy, data transparency, and evidence-based policies. The recommendations proposed are optimizing public-private partnerships, improving the quality of integrated social welfare data, and strengthening sustainable economic empowerment programs